Study on the Static Performance of Prefabricated UHPC-Steel Epoxy Bonding Interface - Yang Zou; Jinlong Jiang; Zhixiang Zhou; Xifeng Wang; Jincen Guo (Advances in Civil Engineering)
Prefabricated UHPC-steel composite structure can make full use of the two materials’ mechanical and construction performance characteristics, with super mechanical properties and durability, which has been proved to be a very promising structure. However, using traditional mechanical connectors to connect prefabricated UHPC and steel not only is inconvenient for the prefabrication of UHPC components but also introduces heavy welding work, which is detrimental to the construction speed and antifatigue performance of the composite structure. Bonding UHPC-steel interface with epoxy adhesive is a potential alternative to avoid the above problem. In order to explore the mechanical properties of the prefabricated UHPC-steel epoxy bonding interface, this study carried out the direct shear test, tensile test, and tensile-shear test of the UHPC-steel epoxy-bonded interface (prefabricated UHPC-steel epoxy bonding interface). The results show that the interface failure is mainly manifested as the peeling of the epoxy-UHPC interface and the destruction of part of the UHPC matrix (the failure of the UHPC's surface). In pure shear and pure tension state, the interfacial shear strength is 5.14 MPa and the interfacial tensile strength is 1.18 MPa. In the tensile-shear state, the interfacial shear strength is 0.61 MPa and the interfacial tensile strength is 1.06 MPa. The stress-displacement curves of the interface normal and tangential direction are all in the shape of a two-fold line. The ultimate displacement was within 0.1 mm, showing the characteristics of brittle failure. Finally, a numerical model of the tensile specimen is established based on the cohesive interface element, and the interfacial tensile-shear coupling failure mechanism (tensile-shear coupling effect) is analyzed.